Safety Climate and Occupational Stress According to Occupational Accidents Experience and Employment Type in Shipbuilding Industry of Korea - Kyung Woo Kim; Sung Jin Park; Hae Sun Lim; Hm Hak Cho (Elsevier, 2017)
Background: Safety climate and occupational stress are related with occupational accident. The present study tried to identify the differences in safety climate and occupational stress according to occupational accidents experience and employment type (e.g., direct workers and subcontract workers). Methods: In this study, we conducted a survey using safety climate scale and Korean Occupational Stress Scale and classified the participants into four groups: direct workers working for accident-free departments, direct workers working for accident departments, subcontract workers working for accident-free departments, and subcontract workers working for accident departments for 2 years within the same workplace in the shipbuilding industry. Results: The direct workers and subcontract workers showed diverse results in subscales of safety climate and occupational stress. This result is supported by existing studies; however, further study is necessary for more supporting evidence and elaborative methodological approach. Conclusion: The necessity of management for safety climate and psychosocial factor such as occupational stress for both direct workers and subcontract workers as a whole is suggested by this study.